6-[(E)-3,7-Dimethyl-octa-2,6-dien-yl]-5,7-dihydr-oxy-8-(2-methyl-butano-yl)-4-phenyl-2H-chromen-2-one from Mesua kunstleri King (Kosterm). - Chan, G.; Awang, Khalijah; Hadi, A.H.A.; Ng, Seik Weng (International Union of Crystallography, 2008)
The title compound, C(30)H(34)O(5), crystallizes with two symmetry-independent mol-ecules in the asymmetric unit. In the crystal structure, the two independent mol-ecules are disposed about a pseudo-center of inversion. An intra-molecular O-H⋯O hydrogen bond is observed in each independent mol-ecule. The crystal structure is stabilized by C-H⋯O hydrogen bonds.